2000
DOI: 10.1136/bmj.321.7268.1043
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of midwife led debriefing to reduce maternal depression after operative childbirth

Abstract: Objective To assess the effectiveness of a midwife led debriefing session during the postpartum hospital stay in reducing the prevalence of maternal depression at six months postpartum among women giving birth by caesarean section, forceps, or vacuum extraction. Design Randomised controlled trial. Setting Large maternity teaching hospital in Melbourne, Australia. Participants 1041 women who had given birth by caesarean section (n = 624) or with the use of forceps (n = 353) or vacuum extraction (n = 64). Main o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
146
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(163 citation statements)
references
References 18 publications
8
146
1
3
Order By: Relevance
“…Conversely, in a larger and well-executed Australian trial involving 1041 women who had operative deliveries, inhospital midwife-led debriefing had a negative effect (25). In particular, more women allocated to the debriefing group exhibited depressive symptomatology (n = 81, 17%) at 24 weeks postpartum, compared with women allocated to usual postpartum care (n = 65, 14%), though the difference was not significant (odds ratio [OR] 1.24; 95%CI, 0.87 to 1.77).…”
Section: Psychological Debriefingmentioning
confidence: 91%
“…Conversely, in a larger and well-executed Australian trial involving 1041 women who had operative deliveries, inhospital midwife-led debriefing had a negative effect (25). In particular, more women allocated to the debriefing group exhibited depressive symptomatology (n = 81, 17%) at 24 weeks postpartum, compared with women allocated to usual postpartum care (n = 65, 14%), though the difference was not significant (odds ratio [OR] 1.24; 95%CI, 0.87 to 1.77).…”
Section: Psychological Debriefingmentioning
confidence: 91%
“…First, studies consistently find that women like postnatal debriefing and evaluate it as helpful (Small et al, 2000). It fits well with a stepped-care treatment approach and offers the opportunity to identify women who need referral forfurther psychological treatment.…”
Section: Introductionmentioning
confidence: 79%
“…Six RCfs have evaluated postnatal debriefing using a range of eligibility criteria and outcomes. Four trials found debriefing had no effect on outcomes such as depression, PTSD, quality of life, parenting stress, or fear of childbirth ( Kershaw, jolly, Bhabra, & Ford, 2005;Priest, Henderson, Evans, & Hagan, 2003;Selkirk, McLaren, Ollerneshaw, McLachlan, & Moten, 2006;Small, Lumley, Donohue, Potter, & Waldenstrom, 2000;Small, Lumley & Toomey, 2006). In contrast, two trials found postnatal debriefing was effective (Gamble et al,2005;Lavender & Walkinshaw, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…76 Following delivery, women were randomized to either receive a debriefing session (n = 520) to discuss their labour, birth and post-delivery events/experiences prior to discharge or standard care (n = 521), which consisted of a brief visit by the midwife to give the mother a pamphlet on sources of assistance. Maternal depression and overall health status (bodily pain, mental and general health, vitality, physical and social functioning, as well as both physical and emotional role functioning) were measured with the Edinburg Postnatal Depression Scale and the 36-item short-form health survey (SF-36), respectively, at 6 months postpartum.…”
Section: -74mentioning
confidence: 99%